Response of early-cycle common bean cultivars with carioca, black and speckled grains to top-dressing nitrogen fertilization (Bioscience Journal, 2023)
The aim was to evaluate the agronomic and qualitative attributes of early-cycle common bean cultivars with different grains types grains in response to top-dressing nitrogen (N) doses. The experiment was carried out using a randomized block design, in a split-plot scheme, with 4 replicates. The plots consisted of the cultivars IAC Nuance, IAC 1849 Polaco and IAC Veloz, with speckled, Carioca and black grains, respectively. The subplots were formed by N doses applied as top-dressing: 0 kg ha-1, 60 kg ha-1 (applied in the stage of third trifoliate leaf), 120 kg ha-1 (1/2 applied at third trifoliate leaf stage + 1/2 applied at the floral bud stage) and 180 kg ha-1 (1/3 applied at the first trifoliate leaf stage + 1/3 applied at the third trifoliate leaf stage + 1/3 applied at the floral bud stage). IAC Veloz stood out for grain yield, showing the highest grain yield in the lowest N doses, being classified as efficient to the use of N. The cultivars IAC Nuance and IAC 1849 Polaco reached maximum yields with 155 and 163 kg ha-1 of N. The IAC Nuance was the most responsive, increasing grain yield by up to 25.3% due to nitrogen fertilization. Increasing N doses applied as top-dressing increased the sieve yield and crude protein content of the common bean cultivars, with IAC Nuance standing out. The cultivars showed good grain quality, and IAC 1849 Polaco and IAC Veloz had the shortest cooking time and IAC Veloz also had the fastest hydration.